Instrument Validation: Self-Efficacy In K-Pop Dance Cover - et. al., Dinny Devi Triana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the instruments of self-efficacy and learning independence in K-Pop Dance Cover Learning. This instrument was used by 66 K-Pop dance cover students at the K-star Academy. The instrument was analyzed quantitatively with the Rasch Model approach using Winsteps software. The result of this research is the availability of an appropriate instrument to measure students' self-efficacy in learning K-Pop Dance, which fulfils the requirements as a valid, reliable instrument.